DISTURBANCE WITH TURBOCHARGER IN INDUCTION MOTORS - Jainuddin Jainuddin; Andi Ernie Zaenab Musa (Indonesian Journal Of Maritim Review, 2023)
Maintenance that involves attention, supervision, maintenance, repair and human power factors as the implementing operator in creating conditions ready for operation of a ship's main propulsion engine whose principles require good handling and maintenance is expected to support shipping operations that have been planned by shipping companies The purpose of this study is to study, solve the formulation of problems regarding turbo chargers on MT. CALAGUAS. This Scientific Writing research method is supported by some accurate data, facts, and information relevant to its title. The research methods that the writing uses are field research, observation, interviews, and library research. The results showed that Surging occurs because the air pressure in the rinse chamber is greater than the air pressure in the blower where this air pressure difference causes a backwave coming from the rinse chamber to the blower at that time. This backwave clashed on the side of the blower, which was marked by a sound like crying. Such conditions will last until there is an air pressure equation in the rinse air